A Cross Sectional Study on Prevalence of Bovine Tuberculosis of Buffaloes in Bangladesh (Microbes and Health, 2013)
This study was conducted to determine the prevalence of bovine tuberculosis in buffalo population in Bangladesh by Caudal Fold Tuberculin (CFT) test using bPPD and also by Comparative Cervical Tuberculin (CCT) test using both bPPD and aPPD. The percentage of reactors was 6.12% in CFT, whereas the percentage of positive buffaloes was 4.08% by CCT method. The percentage of suspicious buffaloes was 10.20% by CFT. On the other hand, all the suspicious cases were proved as misleading-false-reactions in CCT. By CCT method, the male buffaloes (6.25%) showed more positivity to tuberculosis than the female buffaloes (3.03%) of the same area. In contrast, the result found by CFT method was more or less similar (20%) for both male and female buffaloes. Young buffaloes (6-30 months) were more susceptible to tuber-culosis than older buffaloes. It might be suggested that a well coordination in activities should be taken among the public health and Veterinary public health organelles for complete eradication of the disease from the country.DOI: http://dx.doi.org/10.3329/mh.v1i1.13709 Microbes and Health Vol.1(1) June 2012 pp.23-26